Pelatihan dan Edukasi Pembuatan Sabun Cair Cuci Piring dari Daun Pandan Wangi - Ria indah Kusuma Pitaloka (CV. Agrapana Media, 2025)
The Training and Education Activity on Making Liquid Dish Soap from Fragrant Pandan Leaves aims to increase public knowledge, skills, and awareness regarding the use of natural ingredients as an alternative environmentally friendly household product. This program is carried out through stages of socialization, training or counseling, evaluation, and sustainable assistance using a hands-on training approach and direct demonstrations. Participants are taught the process of making liquid soap from fragrant pandan leaves, from extraction, mixing of ingredients, packaging, to product labeling, while also being provided with knowledge on simple marketing strategies. The activity was attended by 20 participants consisting of housewives and students, who were enthusiastic in participating in the entire series of training. The evaluation results showed a significant improvement in understanding the stages of production, workplace cleanliness, product consistency, and packaging creativity, with an average increase of 54% compared to the pre-test. In addition to providing practical skills, this activity encourages participants to develop business opportunities based on local potential and fosters awareness of the importance of eco-friendly products. Continued mentoring and the development of participants as trainers in their respective communities are expected to ensure the sustainability of the program and broaden its positive impact on society. These results indicate that training based on natural materials can be an effective strategy for community empowerment, local economic improvement, and environmental preservation.